Pregnancy Complications and Cardiovascular Disease Death. Issue 13 (29th September 2015) - Cirillo, Piera M.; Cohn, Barbara A.
<x xml:space="preserve">Abstract</x> Background— Few studies have investigated the combination of pregnancy complications that predict risk for cardiovascular disease (CVD) death and how risk changes with age. This report presents a comprehensive investigation of the relation of the occurrence of multiple pregnancy complications to CVD death over 5 decades in a large pregnancy cohort. Methods and Results— We examined pregnancy events (1959–1967) and CVD death through 2011 in 14 062 women from the Child Health and Development Studies. CVD death was determined by linkage to California Vital Statistics and National Death Index. Women were a median age of 26 years at enrollment and 66 years in 2011. Preexisting hypertension (hazard ratio, 3.5; 95% confidence interval, 2.4–5.1); glycosuria (hazard ratio, 4.2; confidence interval, 1.3–13.1); late-onset preeclampsia (after week 34, hazard ratio, 2.0; confidence interval, 1.2–3.5); and hemoglobin decline over the second and third trimesters (hazard ratio, 1.7; confidence interval, 1.2–2.7) predicted CVD death. Delivery of a small-for-gestation or preterm infant and early-onset preeclampsia (by week 34) significantly predicted premature CVD death (P<0.05 for age dependence). Preterm birth combined with hemorrhage, gestational hypertension, or preexisting hypertension identified women with a 4- to 7-fold increased risk of CVD death. Preeclampsia in combination with preexisting hypertension conferred a significant nearly 6-fold risk in comparison with a 4-fold risk for preexisting hypertension alone. Conclusions— We observed combinations of pregnancy complications that predict high risk of death and 2 new risk markers, glycosuria and hemoglobin decline. Obstetricians serve as primary care physicians for many young women and can readily use these complications to identify high-risk women to implement early prevention.